Understanding the Increased Fruit Content of Soluble Proteins, Sugars, Certain Enzyme Activities, and Certain Polyphenols in Context to Date Fruit Ripening - Saad Salman M. Alqarni; Mohammad D Bazzi (ANNALES BOGORIENSES, 2019)
Introduction: To understand the increased fruit content of soluble proteins, sugars, certain enzymes activities, and certain polyphenols in context to date fruit ripening. Materials and Methods: The study collected four varieties of date fruits from a farm in Riyadh, Saudi Arabia. In it, 10-14-day intervals separated the various stages of maturity. The process of sample preparation and extraction includes the samples of fruits at different stages of maturation. Results and Discussion: The Polyphenols oxidize activity appeared to decline with further maturation of date fruit. There was an increase in the protein content and the reducing sugar in all varieties of dates. The changes in the total sugar and reducing sugar occurred due to the increased enzyme’s activity. Conclusion: The reducing sugar increased in all varieties of the date fruit. The coordination of the enzyme might influence the quality of the ripening of date fruits.